Avtur Waste Treatment to Produce Useful Fuel Products based on ASTM Standard - Dwi Nurhudaeni; Zakir Sabara; Andi Suryanto; Belda Amelia Junisu; Iva Yenis Septiariva; Riza Aldiansyah Fanani (CV FOUNDAE, 2022)
The many avtur samples that are tested every month has an impact on avtur waste that accumulates in the PT. Pertamina Lubricant PU Jakarta laboratory. Avtur wastes are usually just thrown away without being processed again. This study focuses on the utilization of avtur test results waste by knowing the quality of avtur waste with flash point, distillation, freezing point, density and color test parameters. The aims of this research are to solve the problem of waste from avtur testing results by reusing avtur waste to become a product so as to reduce the occurrence of losses. The first step is to prepare a sample of waste from avtur test results and then perform tests on the flash point, distillation, freezing point, density and color test parameters. After that, avtur waste was formulated: avtur ASTM standard T.107 with variations in the formulation, namely 5% LA : A, 10% LA : A, 15% LA : A and 20% LA : A. After that, the mixing process was carried out for 15 minutes using a stirrer motor with a speed of 300 rpm (rotations per minute). Then flash point, distillation, freezing point, density and color tests were carried out to get results that match the specifications of the avtur. The results showed that the formulation of the avtur test results: avtur according to American Standard Testing and Material (ASTM) standard had met the avtur specifications. Where the best formulation was found in 10% avtur waste formulation with test value of color : 25, density : 802.4 Kg/m3, flash point : 42.5 oC, freezing point : -55.0 oC and distillation (IBP : 156.0 oC, 10 % : 172.0 oC, 50% : 194.0 oC , 90% : 225.0 oC, End Point : 257.0 oC. Based on the results of the formulation testing that has been carried out, the avtur test results formulated with ASTM standard for avtur have met the company's quality standards.